A cross-sectional pilot study to define anal cancer risk factors in HIV-positive solid organ transplant recipients - I. Fuertes; I. Chivite; R. D. Cranston; E. Sanchez; E. De Lazzari; L. Marimón; J. Ordi; J. M. Miro; J. L. Blanco (Infectious Diseases, 2026)

Incidence and risk factors of surgical site infection in dogs undergoing laparoscopy ovariectomy. Multicentric prospective cohort study - M. Fuertes-Recuero; J. Espinel Rupérez; M. Abal-Flores; G. Gonzalez-Matellano; M. Gardoqui-Arias; A. Rubio Guivernau; A. Fraile-Fernandez; D. Carrero Escolar; C. Sánchez-Collado; D. Calzado-Barranco; J.C. Fontanillas-Pérez; G. Ortiz-Diez (The Veterinary Journal, 2025)

Optimization of the Polarized Imaging Nephelometer (PI-Neph) for continuous monitoring of multiwavelength aerosol phase functions in support of space polarimetry missions - E. Bazo; J.V. Martins; D. Perez-Ramirez; A. Valenzuela; G. Titos; A. Cazorla; D. Fuertes; M. Weiss; A. Turpie; C. Li; F.J. García-Izquierdo; I. Foyo-Moreno; et al. (Atmospheric Environment, 2024)

Assessing the potential of poplar short rotation plantations to contribute to a low-carbon bioeconomy under water-limited conditions - A. Fuertes; N. Oliveira; I. Cañellas; H. Sixto; R. Rodríguez-Soalleiro; M. Hanewinkel; D. Sperlich (Journal of Environmental Management, 2023)

Public Procurement for the Circular Economy: a Comparative Study of Sweden and Spain - Leticia Fuertes Giné; Emanuela Vanacore; Agnieszka D. Hunka (Circular Economy and Sustainability, 2022)
This article examines the relationship between circular economy and public procurement by regarding green procurement as an enabler for the transition from sustainable to circular public procurement. Considering the different green procurement uptakes under the common legal framework of the European Union, and particularly, the contrasting practice results of Spain and Sweden and the opposed legal configuration of their procurement Acts, a comparative law study of the exclusion of suppliers, awarding criteria and special conditions of performance’s Articles is conducted.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Impact of universal access to hepatitis C therapy on HIV-infected patients: implementation of the Spanish national hepatitis C strategy - A. Rivero-Juarez; L. F. Lopez-Cortes; M. Castaño; D. Merino; M. Marquez; M. Mancebo; F. Cuenca-Lopez; P. Jimenez-Aguilar; I. Lopez-Montesinos; S. Lopez-Cardenas; A. Collado; M. A. Lopez-Ruz; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Dimension of chronic hepatitis C virus in HIV-infected patients in the interferon-free era: an overview from south Spain - A. Rivero-Juarez; A. Gutierrez-Valencia; M. Castaño; D. Merino; K. Neukam; M. J. Ríos-Villegas; M. A. Lopez-Ruz; P. Jiménez-Aguilar; M. Marquez; A. Collado; A. Gomez-Vidal; J. Hernandez-Quero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Effects of varying protein level in practical diets on survival, growth, feed utilization and body composition of juvenile tench (Tinca tinca L.) - Á. González-Rodríguez; J. D. Celada; J. M. Carral; M. Sáez-Royuela; J. B. Fuertes (Aquaculture International, 2014)

Design of Water Distribution Networks using a Pseudo-Genetic Algorithm and Sensitivity of Genetic Operators - D. Mora-Melia; P. L. Iglesias-Rey; F. J. Martinez-Solano; V. S. Fuertes-Miquel (Water Resources Management, 2013)